Enhancing Students’ Learning Engagement and Academic Writing Ability through Challenge-Based Gamification Lessons - Chavangklang, Thanaset; Chavangklang, Pitchayapa (Ratchaphruek Journal, 2024)
The objectives of the study were to: 1) assess the level of academic writing ability and learning engagement; 2) compare academic writing ability before and after the use of challenge-based gamification lessons; 3) examine the relationship between academic writing ability and learning engagement during gamified lessons; and 4) determine student satisfaction with the challenge-based gamification approach. Sixty-five second-year students from Nakhon Ratchasima Rajabhat University participated in a 15-week Academic Writing course during the first semester of 2022, which included gamified elements such as points, leaderboards, and weekly challenges. Data collection involved pre-test and post-test assessments of writing ability and questionnaires on student satisfaction. Results showed a significant improvement in writing ability, with post-test scores increasing from an average of 7.76 to 16.04 out of 25. Learning engagement, as measured by experience points, averaged 546.09, ranging from 96 to 1,667 points. A Pearson correlation coefficient of 0.208 revealed a weak positive relationship between learning engagement and writing ability, accounting for 4.31% of the variance in writing outcomes. Students expressed high satisfaction with the gamified lessons, especially regarding achievement, guidance, and enjoyment. These findings indicate that challenge-based gamification is effective in enhancing academic writing skills and fostering a positive learning experience.